Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning di Kelas V SD - Alvionita, Kika; Abidin, Zainal (Universitas Negeri Padang, 2021)
This research purposed to describe the improvement of integrated thematic learnig process using cooperative learning model Talking Stick type in Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 28 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection . The result of planning observation in cycle I is 78% and it increase to be in cycle II 94% . The result of teacher aspect observation in cycle I is 76,5% and it increase to be 84% . in cycle II. The result of student aspect observation in cycle I is 76,5 % and it increase to be 84%. in cycle II. The research showed the cooperative learning model Talking Stick type can improve the integrated thematic learnig process in Elementary School.